Komponen Pariwisata 4A (Attraction, Accessibility, Amenities, Ancillary) di Daya Tarik Wisata Gunung Payung Cultural Park - Panuntun, Dena Conchita; Mahagangga , I Gusti Agung Oka (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Gunung Payung Cultural Park is a tourist attraction which currently experiencing development both in terms of tourist visits and the attraction itself. This research was conducted in order to identify the 4A tourism components (Attraction, Accessibility, Amenities, and Ancillary) of Gunung Payung Cultural Park. This research uses qualitative data which collected through observation, interviews, documentation, and literature study. The data in this study were analyzed using qualitative descriptive techniques or making descriptions in the form of narratives based on the obtained qualitative data. The results of this study are in the form of an explanation regarding the availability of the 4A tourism components in Gunung Payung Cultural Park.